Effect of serving factors of milk powder in sachet packaging on total microbial - Dwi A. Ratih; . Nurliana (Syiah Kuala University, 2012)
The aim of this research was to study the microbial quality of milk powder based on the serving factors during milk powder serving process. The method used in this research was Total Plate Count (TPC). Nine sachets (400 g/sachet) of milk powder was used as many as This experiments used Split Plot Design, comprised three factors, storage factor (P1, P2 and P3), time of serving factor (morning and evening), and shelf life factor (day of 1st-7th). Each treatment consisted of three sachets of milk powder. Storage factors comprised P1 (sachets packaging contained of milk powder were placed into the glass bottle container), P2 (sachets packaging contained of milk powder were placed into glass botlle with spoon inside, and P3 (sachets packaging contained of milk powder with spoon inside were not placed into the glass bottle container). The results of this research showed that storage factors and time of serving did not sifnificantly (P0,05) affect on the microbial count of milk powder, but shelf life factor significanly (P0,01) affected on microbial count of milk powder at day of 1th and 7th. Milk powder in sachet packs (400 grams) has been opened, with or without spoon in the sachet and more than five days of shelf life can increase the total number of microbes, which was exceed TPC decision at 5x104 CFU/grams of milk powder.